Movies under the influence - Szczepaniak-Gillece, Jocelyn (University of Minnesota Press, 2024)
"Exploring the effects of intoxicants on film spectatorship, Movies under the Influence charts their entangled histories from early cinema through the psychedelic 1970s. Jocelyn Szczepaniak-Gillece examines the implicit relationship mind-altering substances suggest between mass media, spectatorship, and governmental regulation, offering a new angle from which to understand cinema's lasting role in evolving American culture"-- Provided by publisher.
Keywords: Drugs in motion pictures.; Motion pictures -- United States -- History -- 20th century.; Médicaments au cinéma.; Cinéma -- États-Unis -- Histoire -- 20e siècle.; PERFORMING ARTS / Film / History & Criticism